Adjustment of Daily Activities: the Influence of Smartphone Adoption on the Travel Pattern of Mobile Professionals in the Greater Jakarta Area - Christin, Gloriani Novita; Tamin, Ofyar Z.; Santosa, Idwan; Miharja, Miming (ITB Journal Publisher, LPPM ITB, 2014)
The swift augmentation in the adoption of smartphones, the gadget that resulted from the convergence of Information and Communication Technology (ICT), potentially transforms peoples life in myriad dimensions. One potential change induced by smartphones, is how people restructure their daily agenda and consecutively influence their travel pattern. To understand it, this study theoretically reviews mobile professional work, smartphone adoption, and how people conduct their mobile interaction, planning and execution of daily activities. Mobile professionals, the cohort of professionals that spend more than 20% of their total working time moving around out of their work environment; they are important beneficiaries of smartphones and have been chosen as the target of this study. Empirical results of mobile professionals´ experiences in the Greater Jakarta Area are presented at this juncture. Furthermore, their adjustment of activities as a dynamic response to receiving extensive information via smartphones is also analysed. The results indicate that there is a strong adjustment of daily activities by mobile professionals. Through those changes, the transformation of daily travel patterns related to the activity is also brought about by the use of this high-end ICT contrivance.